A Review on Performance Improvement of Wireless System via Smart Antennas (International Journal of Engineering and Computer Science, 2014)
Smart antennas have made great progress in field of communication.There are different working principles for different types of antennas in use. Each type of antenna has its own advantages and applications. It has applications in different areas wireless network system or OFDMA etc. Smart antennas enhance the capability of a mobile and cellular system. Smart antennas also help SDMA (Space division multiplexing) to increases in range. Multi path mitigation reduces the errors because of multi path fading concept of smart antennas. It also has one big advantage that is it has very high security.